1998
DOI: 10.1074/jbc.273.48.31971
|View full text |Cite
|
Sign up to set email alerts
|

Ssp1, a Site-specific Parvulin Homolog from Neurospora crassa Active in Protein Folding

Abstract: Peptidyl-prolyl cis-trans-isomerasesHere we describe the purification and characterization of Ssp1, an abundant parvulin homolog from Neurospora crassa, which is unique among the known eucaryotic parvulins in containing a polyglutamine stretch between the N-terminal WW domain and the C-terminal PPIase domain. Ssp1 is a site-specific PPIase with respect to the amino acid N-terminal to the proline residue. Peptides with glutamate, phosphoserine, or phosphothreonine in the ؊1-position proved to be the best substr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
28
1

Year Published

2000
2000
2001
2001

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 50 publications
1
28
1
Order By: Relevance
“…The described PIN1At protein lacks the N-terminal domain but contains a sequence that is highly homologous to the PIN1 ␣1 helix. Furthermore, preliminary structural data by circular dichroism and conformational 13 C␣ chemical-shift deviations from random coil values are consistent with this stretch being in a helical conformation. Functionally, the role of a protein-protein interaction module was initially recognized for the WW domains (14), but only very recently has it been shown that the PIN1 WW domain interacts specifically with a number of proteins phosphorylated on one or more serine or threonine residues (17).…”
Section: Pin1at (This Work) Is From a Thaliana (Accession Number Aadmentioning
confidence: 54%
See 2 more Smart Citations
“…The described PIN1At protein lacks the N-terminal domain but contains a sequence that is highly homologous to the PIN1 ␣1 helix. Furthermore, preliminary structural data by circular dichroism and conformational 13 C␣ chemical-shift deviations from random coil values are consistent with this stretch being in a helical conformation. Functionally, the role of a protein-protein interaction module was initially recognized for the WW domains (14), but only very recently has it been shown that the PIN1 WW domain interacts specifically with a number of proteins phosphorylated on one or more serine or threonine residues (17).…”
Section: Pin1at (This Work) Is From a Thaliana (Accession Number Aadmentioning
confidence: 54%
“…Spectra were recorded from 180 to 250 nm using a 0.1-and 1-mm path length cell at 20°C. Backbone carbon and hydrogen resonances were assigned from a set of triple resonance NMR experiments (19) recorded on a 1-mM 13 C, 15 N-labeled PIN1At sample in 50 mM deuterated Tris-Hcl, pH 6.3, 100 mM NaCl, 1 mM dithiothreitol, 1 mM PMSF, and 0.5 mM EDTA using a DMX 600-MHz spectrometer (Bruker, Karlsruhe, Germany).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the dephosphorylation of a protein or peptide by PP2A can be dramatically influenced by the PPIase activity of Pin1, which apparently converts cis pSer/pThr-Pro bonds in the substrate into PP2A-accessible trans peptide bonds (31). Furthermore, a function in protein folding has been suggested for the N. crassa protein Ssp1, because it is able to accelerate the refolding of urea-denatured dihydrofolate reductase in vitro (15).…”
mentioning
confidence: 99%
“…Among this family are the highly conserved Pin1-type PPIases (10,11), which are the only PPIases that seem to be essential for cell survival, at least in budding yeast and HeLa cells. The Pin1-type PPIases, such as the human Pin1 (11), Saccharomyces cerevisiae ESS1/Ptf1 (10,12,13), Drosophila Dodo (14), Neurospora crassa Ssp1 (15), Xenopus Pin1 (16), Aspergillus nidulans Pin1 (17), and others, consist of an amino-terminal WW domain and a carboxyl-terminal PPIase domain. WW domains, which are characterized by two invariant tryptophans, are present in a variety of signaling and regulatory proteins and were originally identified as protein interaction modules that bind to proline-rich regions in protein targets (18,19).…”
mentioning
confidence: 99%